Enhanced Susceptibility to Citrobacter rodentium Infection in MicroRNA-155-Deficient Mice - Clare, Simon (American Society for Microbiology, 2013)
MicroRNAs (miRNAs) are small noncoding molecules that control gene expression posttranscriptionally, with microRNA-155 (miR-155) one of the first to be implicated in immune regulation. Here, we show that miR-155-deficient mice are less able to eradicate a mucosal Citrobacter rodentium infection than wild-type C57BL/6 mice. miR-155-deficient mice exhibited prolonged colonization associated with a higher C. rodentium burden in gastrointestinal tissue and spread into systemic tissues. Germinal center formation and humoral immune responses against C. rodentium were severely impaired in infected miR-155-deficient mice. A similarly susceptible phenotype was observed in μMT mice reconstituted with miR-155-deficient B cells, indicating that miR-155 is required intrinsically for mediating protection against this predominantly luminal bacterial pathogen.